MIKROZONASI BAHAYA GEMPA BUMI DI WILAYAH KOTA BANDUNG BERDASARKAN DATA MIKROTREMOR - Marjiyono Marjiyono; Afnimar Afnimar (Pusat Survei Geologi, 2011)
Bandung is one of the metropolitan city which rapidly developed and tectonically located in the vicinity of active tectonic lines. The surface geology condition of this region vary from very soft sediments to hard volcanic rocks. The soft sediment area has potential to experience amplification when an earthquake occure. Characterization of surface geology is necessary to identify vulnerability level in order to mitigate the earthquakes hazard in this region. In this regard, we have conducted microtremor measurements in 97 sites which are spread throughout the city of Bandung. Data processing is based on the Nakamura method (HVSR) to obtain the value of amplification factor. The results show the value of amplification factor ranged from 2.1 to 17, with the highest amplification factor distribution in the southeastern of the research area. Distribution of this very high amplification factors are broadly corresponded with lacustrine sediment (lake sediment). The amplification factor scores were then used as the basis in determining the level of relative vulnerability to earthquake hazards.Keywords : microtremor, effect of surface geology, amplification factor, Nakamura methods.